Evaluation of the genetic parameters for 10 common and five new ESS core autosomal STR loci in seven major geographic regions and the largest metropolitan province of Turkey - Kemal Murat Canturk; Cemal Gurkan; Huseyin Sevay; Ramazan Emre (Taylor & Francis Group, 2017)
Background: Situated at the crossroads of Asia, Middle East and Europe, Turkey has an ethnically diverse population of over 78 milllion people. Aim: To investigate the population genetics and potential differences in the autosomal short tandem repeat (STR) polymorphisms across all the major geographic regions and largest metropolitan province of Turkey within the context of the Near Eastern/European genetic landscape. Subjects and methods: Samples from a total of 5299 unrelated individuals were analysed at 10 common [D2S1338, D3S1358, D8S1179, D16S539, D18S51, D19S433, D21S11, FGA, TH01, vWA] and five new European Standard Set (ESS) core autosomal STR loci [D1S1656, D2S441, D10S1248, D12S391, D22S1045]. Results: Allele frequencies, statistical parameters of forensic interest and population differentiation tests were calculated for nine population datasets corresponding to the seven major geographic regions, the largest metropolitan province, and a combined dataset for the entire country. Cumulative results confirmed the presence of significant differences among these nine autosomal datasets themselves and with those from the nearby populations, therefore justifying the differential use of these separate datasets on a case-by-case basis in forensic investigations. Conclusion: This collection of autosomal STR population datasets comprises the largest and most comprehensive of its kind from Turkey so far.